Pengaruh Motivasi Belajar Dan Gaya Hidup Hedonisme Terhadap Prestasi Belajar Mahasiswa Universitas Ibnu Sina Batam - Kamaruddin Kemaruddin; Andi Tenri Ummu; Haji Mustaqim (LPPM Universitas Jambi, 2022)
The purpose of this study is to find out the influence of learning motivation and hedonism lifestyle on student learning achievement. The population of this study is a student of Ibn Sina Batam. The population in the study was 554 students. The sample was calculated using the slovin formula, so the sample used in the study was as many as 92 respondents. The results of this study are motivation has a significant effect on student learning achievement, hedonism lifestyle has a significant effect on student learning achievement, and simultaneously learning motivation and hedonism lifestyle have a significant effect on student learning achievement. The R square score of 53.1% means that learning motivation and hedonism lifestyle can affect student learning achievement by 53.1% while the remaining 46.9% is influenced by other factors.